2010
DOI: 10.1073/pnas.0914096107
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals extreme egg morphology and nesting behavior in New Zealand’s extinct moa

Abstract: New Zealand's extinct flightless moa radiated rapidly into a large number of morphologically diverse species, which produced an equally large range of egg morphologies. The exact number of moa species, as well as the characteristics of the eggs they laid, remains contentious. Moreover, like most extinct species, we understand little about their nesting and incubation habits. We used a modified ancient DNA extraction procedure to recover exogenous mitochondrial and nuclear DNA from the inside and outside surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 21 publications
7
55
1
1
Order By: Relevance
“…Thus thickness was shown to be a poor discriminator of taxa. Oskam et al (2011) noted that their data did not support two clades of Euryapteryx as suggested by Huynen et al (2010).…”
Section: Moa Breeding: Nests and Eggsmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus thickness was shown to be a poor discriminator of taxa. Oskam et al (2011) noted that their data did not support two clades of Euryapteryx as suggested by Huynen et al (2010).…”
Section: Moa Breeding: Nests and Eggsmentioning
confidence: 98%
“…Therefore, it would be expected that Euryapteryx shell from Oamaru, South Island, would be on average thicker than shell from the Far North (northern North Island) in the one taxon. This expectation is met to an extent, with the thinner shell, all that B1.0 mm, being from the Far North; however, Huynen et al (2010): supplementary information) found that some of the thick shell was derived from the Far North (Tokerau Beach, Matai Bay and North Cape).…”
Section: Moa Breeding: Nests and Eggsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the observation of an even sex ratio among juvenile moa of the taxon Euryapteryx curtus (Allentoft et al, 2010), but not among the adults, a higher mortality among males has also been suggested. Incubation by males has been suggested by Huynen et al (2010) who identified putative moa male DNA on the surface of their eggshell.…”
Section: Introductionmentioning
confidence: 99%